PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN RESTORAN WARUNG TAULAN BADUNG - ., ZULKARNAEN; Sudarma, I Nyoman (E-Jurnal Manajemen; Vol 7 No 1 (2018)DO - 10.24843/EJMUNUD.2018.v7.i01.p13, 2018)
The purpose of this study is to determine the effect of leadership style and financial compensation on job satisfaction employees of Restaurant Warung Taulan Badung. This research is quantitative associative. Sources of data used in this study are primary and secondary data. The method of determining the sample in this study is the sample saturated, so the sample in this study is the same with the number of population is 31 people. Data collection techniques used interviews and questionnaires. Data analysis technique used multiple linear regression analysis. The results showed that tranformational leadership and compensation have a positive and significant effect on employee job satisfaction Restaurant Warung Taulan Badung.